How Are Students' Creative Thinking Skills Through Microbial Growth Rate Worksheet on Nata De Whey Kefir? - Mas'ud, Asrianty; Kurniati, Tuti; Jaelani, Yusuf (Biosfer: Jurnal Tadris Biologi, 2024)
Worksheets can be used as a solution to the success of the practicum process. This study aimed to analyze students' creative thinking skills through worksheets of microbial growth rates on nata de whey kefir. The method used in this research was a Pre-Experimental Design with a one-group pretest-posttest design. The population of this research was the sixth-semester Biology Education Study Program students. The research sample consisted of a class of 21 students selected using a purposive sampling technique. The research instrument consisted of description questions containing indicators of creative thinking. The results of the research data analysis obtained an average N-gain for each indicator of creative thinking skills of 0.461, which was included in the "medium" criteria. Test the data hypothesis using the T-paired test obtained a significance value of 0.000 <0.05. Therefore, H0 was rejected, and H1 was accepted. Based on the research results obtained, data showed that there was an increase in students' creative thinking skills through worksheets on the rate of microbial growth in nata de whey kefir.ABSTRAK: Lembar kerja dapat digunakan sebagai solusi dalam keberhasilan proses praktikum. Penelitian ini bertujuan untuk menganalisis keterampilan berpikir kreatif mahasiswa melalui lembar laju pertumbuhan mikroba pada nata de whey kefir. Metode yang digunakan dalam penelitian ini adalah Pre-Experimental Design dengan desain penelitian one-group pretest-posttest design. Populasi penelitian ini adalah mahasiswa semester VI Program Studi Pendidikan Biologi. Sampel penelitian menggunakan satu kelas yang berjumlah 21 mahasiswa dengan menggunakan teknik purposive sampling. Instrumen penelitian terdiri dari soal uraian yang memuat indikator berpikir kreatif. Hasil analisis data penelitian diperoleh rata-rata N-gain dari setiap indikator keterampilan berpikir kreatif sebesar 0,461 termasuk pada kriteria “sedang”. Data uji hipotesis dengan menggunakan Uji T-paired diperoleh nilai signifikansi 0,000 < 0,05 maka H0 ditolak dan H1 diterima.  Berdasarkan hasil penelitian diperoleh data bahwa terdapat peningkatan keterampilan berpokir kreatif mahasiswa melalui lembar kerja laju pertumbuhan mikroba pada nata de whey kefir.